Parmanu‐Gunak: Data Reduction Software for Isotope Dilution Analysis - Pathak, Dipankar (Geostandards and geoanalytical research, 2023)
Isotope dilution (ID) is a widely used analytical technique to determine elemental abundance to a high degree of accuracy and precision, using a spiked isotope tracer. This technique also enables efficient correction of the inevitable phenomenon of analytical mass fractionation during mass spectrometric analysis. It is also used to determine stable isotope variations of an element in a sample relative to a reference material, using tracers enriched in two isotopes (popularly known as the double spike method). Isotope dilution data reduction can be performed in Microsoft® Excel™ using different algorithmic approaches. Additional software such as iolite and MATLAB® offer algorithm implementations to perform these calculations. These are however limited to use within particular laboratories/research groups, or either require additional cost‐bound software or some degree of knowledge in computer programming languages for use, or all of these. To ease this situation, a graphical user interface‐based software is proposed (here named Parmanu‐Gunak, meaning Atom‐Calculator in Sanskrit text) to invert both single and double spiked isotope data, with the aim of making it a standard tool for ID data reduction. Examples of Nd and Mo isotopes are used to demonstrate the robustness of the program. Key Points Parmanu‐Gunak is free software that offers deconvolution of isotope dilution data in a very user‐friendly approach. Options for both single and double spiked isotope data reduction are included. Parmanu‐Gunak requires no additional software to function and is available for different operating systems.